High-Efficiency and High-Monochromaticity Semitransparent Organic Solar Cells Based on Optical Tamm States - Junwei Zhao; Senxuan Lin; Jinxin Zhou; Fuhao Gao; Jingfeng Liu; Yongbing Long; Haitao Xu (Photonics)
Semitransparent organic solar cells (ST-OSCs) have garnered more interest and stand out as promising candidates for next-generation solar energy harvesters with their unique advantages. However, challenges remain for the advancement of colorful ST-OSCs, such as enhancing the light absorption and transmittance without considerable power conversion efficiency (PCE) losses. Herein, an optical analysis of silver (Ag) electrodes and one-dimensional photonic crystals (1DPCs) was conducted by simulations, revealing the presence of optical Tamm states (OTSs) at the interface of Ag/1DPCs. Furthermore, the spectral and electrical properties were fine-tuned by modulating the OTSs through theoretical simulations, utilizing PM6:Y6 as the active layer. The structural parameters of the ST-OSCs were optimized, including the Ag layer thickness, the central wavelength of 1DPCs, the first WO3 layer thickness, and the pair number of WO3/LiF. The optimization resulted in the successful development of blue, violet-blue, and red ST-OSC devices, which exhibited transmittance peak intensities ranging from 31.5% to 37.9% and PCE losses between 1.5% and 5.2%. Notably, the blue device exhibited a peak intensity of 37.0% and a PCE of 15.24%, with only a 1.5% loss in efficiency. This research presents an innovative approach to enhancing the performance of ST-OSCs, achieving a balance between high transparency and high efficiency.